Improving Critical and Creative Thinking Skills with Articulate Storyline Media in Learning Food and the Human Digestive System in Grade XI - Silviani C. Evangelista Rea; Elsje T. Maasawet; Yusak Hudiyono; Budi Raharjo; Evie Palenewen; Makrina Tindangen (Postgraduate, University of Mataram, 2024)
This development research aims to: (1) prove the feasibility and practicality of articulate storyline media in learning about food and the digestive system (2) to prove that articulate storyline media with problem based learning (PBL) model in learning about food and the digestive system is effective in improving critical and creative thinking skills (3) to prove that articulate storyline media with project based learning (PJBL) model in learning about food and the digestive system is effective in improving critical and creative thinking skills. The type of research used is Research and Development (R&D) with ADDIE development model. The subjects in this study were biology subject teachers and students of class XI MIPA 1 and XI MIPA 2 SMAN 6 Samarinda and class XI MIPA 3 and XI MIPA 4 at SMAN 4 Samarinda. Data testing was carried out by testing the feasibility of the media, the practicality of the media, the effectiveness test using the Manova test and the N-Gain test. The results of the study obtained: (1) articulate storyline media is feasible and practical to be used in the learning process (2) articulate storyline media with problem based learning (PBL) learning model in learning about food and the digestive system is effective in improving critical thinking skills (3) articulate storyline media with project based learning (PJBL) learning model in learning about food and the digestive system is effective in improving creative thinking skills. Based on the manova test, a significance value of 0.000 (sig <0.05) was obtained, so it was concluded that there are learning models that have different abilities in terms of influencing critical thinking skills and creative thinking skills simultaneously.